Peranan Finansial Teknologi, Perilaku Keuangan Terhadap Ketahanan Keuangan Mahasiswa Fakultas Ekonomi Dan Bisnis UNTAG Surabaya - Hana Damayanti Tarihoran; Cindy Septiana Rahayu; Irma Nur Fadlia; Maria Yovita R. Pandin (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
This research aims to understand the role of financial technology in the financial resilience of students from the Faculty of Economics and Business at UNTAG Surabaya. A qualitative research method was employed, with interviews as the data collection technique. The respondents were students from the Faculty of Economics and Business at UNTAG Surabaya who use financial technology in managing their finances. The results indicate that financial technology plays an important role in improving the financial resilience of students. Financial technology facilitates financial access and provides flexibility in financial management. However, there are also risks that need to be considered, such as data security and addiction to the use of financial technology. Therefore, there is a need for responsible use of financial technology and efforts to enhance financial literacy among students.